“Screwed from the start”: How women perceive opportunities and barriers for building a successful research career - Berggren, Åsa; Almlöv, Cecilia; D’Urso, Alexandra; Grubbström, Ann (Frontiers in Education, 2022)
After finishing the PhD, the researcher enters a stage in their early research career where more independence is expected. Within a relatively short time period, the researcher needs to gather research experience and support in the form of tangible resources as funding, and intangible resources like access to research networks, close collaborations, and mentorship to support their next career stage. How resources are allocated are therefore important determinants for the success of researchers. However, research shows that the resource allocation decisions in academia are biased in favor of men, with many of these gender biases that influence the success of research careers increasing. In this study we asked women employed as early-career researchers (WECRs) about how they view their opportunities and potential for long-term success within academia, and how this relates to the resources that they have access to. We found that the WECRs were given few resources and support, and that they perceived that finding resources important for their career was up to themselves. The noticeable male dominance in who receives resources and positions within the university and the lack of women as role-models signals to WECRs that they are not wanted in academia. The researchers suggest several ways to improve the possibilities for the WECRs to work towards a successful research career on more equal terms as their male colleagues: these include transparent processes for resource allocations, equal opportunity officers in all hiring processes, and mandatory gender training for all senior research and administrative staff. All the actions suggested are within the control of the university.